Comparison of different selective enrichment steps to isolate Salmonella sp. from feces of finishing swine Comparação de diferentes etapas de enriquecimento seletivo no isolamento de Salmonella sp. de fezes de suínos de terminação - Geovana Brenner Michael (Brazilian Journal of Microbiology, 2003)
A two-phase study was conducted to compare the efficacy of several enrichment selective-broth steps associated to different plating media for recovery of Salmonella sp. from finishing swine feces. In a first phase, Rappaport-Vassiliadis broth (RV) incubated at 42ºC, Tetrathionate Müller-Kauffmann broth at 37ºC (TMK37) and 42ºC (TMK42), and Selenite Cystine broth (SC) at 37ºC, in combination with three selective plating media Rambach agar (RA), Xylose-Lysine-Tergitol 4 agar (XLT4), and Brilliant-Green Phenol-Red Lactose Sucrose agar (VB) were compared for recovery of Salmonella from artificially contaminated swine feces. In a second phase, RV, TMK37, and TMK42, associated with XLT4 and VB , were tested with naturally contaminated swine feces. In this study RV, TMK42 and TMK37 were superior to SC for isolating Salmonella sp. from artificially contaminated feces. TMK42 and RV were more productive than TMK37 for recovery of Salmonella from naturally contaminated feces samples. Selectivity and indication capability of the plating media were remarkably affected by the selective enrichment step effectiveness. The TMK42/XLT4 association was the most sensitive and RV/XLT4 the most specific. The use of VB agar is also recommended to increase the likelihood of isolating atypical H2S-late producing/ non-producing Salmonella. In this study RV and TMK42 were the most efficient selective enrichment for recovery of Salmonella sp. from swine feces. Através de um estudo em duas fases comparou-se a eficiência de etapas de enriquecimento seletivo, associadas a diferentes meios seletivos, na recuperação de Salmonella sp. de fezes de suínos de terminação. Em uma primeira fase, as amostras foram contaminadas artificialmente e os caldos Rappaport-Vassiliadis (RV) incubado a 42ºC, Tetrationato Müller-Kauffmann a 37ºC (TMK37) e 42ºC (TMK42), e Selenito Cistina (SC) a 37ºC foram testados, em associação com meios sólidos seletivos: ágar Rambach (RA), ágar Xilose-Lisina-Tergitol 4 (XLT4), e ágar Verde-brilhante Vermelho-neutro Lactose Sacarose (VB). Na segunda fase os caldos RV, TMK37, and TMK42, semeados nos meios XLT4 and VB, foram testados com amostras naturalmente contaminadas. No isolamento de Salmonella sp. em amostras artificialmente contaminadas o RV, TMK42 e TMK37 foram superiores ao SC. Na segunda fase o TMK42 e RV foram mais eficientes que o TMK37. O desempenho destas etapas de enriquecimento seletivo influenciou diretamente a capacidade seletiva e indicadora dos meios sólidos seletivos utilizados. No presente estudo, a associação TMK42/XLT4 demonstrou ser a mais sensível, e a RV/XLT4 a mais específica. O uso do meio VB também é recomendado para aumentar a probabilidade do isolamento de colônias atípicas de Salmonella - produtoras tardias ou não produtoras de H2S. No presente estudo, RV e TMK42 foram as etapas de enriquecimento seletivo mais eficientes para o isolamento de Salmonella de fezes de suínos.